Generation of macro-vortices in estuarine compound channels - He, Chang; Yin, Zhen-Yu; Stocchino, Alessandro; Wai, Onyx Wing Hong (Frontiers in Marine Science, 2023)
We report the results of a numerical investigation of the flow structure and mechanism of macro-vortex generation in estuarine compound channels. The Finite-Volume Coastal Ocean Model (FVCOM) was implemented to simulate tidal currents in compound channels, e.g., the Lantau Channel, which lies in the middle of the Pearl River Estuary (PRE). Results showed that the velocity magnitude in channels was significantly larger than that of floodplains during the ebb and flood phases, resulting in a high-velocity gradient at the depth discontinuity. Vorticity and Q-criterion were used to analyze the macro-vortex distribution inside the PRE. Massive macro-vortices were generated along the compound channels where high vorticity was also detected. The across-estuary sections with single and multiple channels were selected as representatives to analyze velocity distribution during ebb and flood tides. To characterize the channel flow, the ratio of the main channel depth of the Lantau Channel to floodplain depth (Rh) was calculated using the topography information and surface elevation of sections. It was found that there existed a channel segment where the flow periodically changed between shallow flow (Rh > 3) and intermediate flow (2< Rh< 3). This dynamic change in Rh greatly influenced the generation of macro-vortices. Transverse dispersive stresses were calculated to evaluate the longitudinal momentum transfer in the lateral direction. We found that the dispersive stresses could play an important role in the redistribution of momentum in addition to barotropic and baroclinic transport. This paper revealed the mechanism of the dynamic generation of macro-vortices in the estuarine compound channel, serving as a valuable example in understanding natural compound channel flows.